CYTOGENETIC EFFECTS INDUCED BY SEEDS OF $ALLIUM~CEPA$ TREATMENT OF POINTS WATERS OF HRAZDAN RIVER (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
The cytogenetic influence of water samples in river Hrazdan (on the territory of Yerevan) in test-object Allium cepa was investigated. 6 points for the collection of water samples were selected. Time and space heterogenicity of clastogenic activity is revealed caused by municipal and technogenic load of Hrazdan river.
Keywords: cytogenetic influence; clastogenic activity; heterogenicity; water samples